Exploring the secondary school dropout risk phenomenon in Kinta Utara district, Perak - Mohammad Faisal, Nurfarah Najwa (2025)
The Ministry of Education Malaysia (MOE) emphasizes the importance of education for all. However, dropout issues remain a problem, especially among secondary school students. The aim of this study is to provide an understanding of at-risk students who drop out using purposive sampling. A total of five schools in the Kinta Utara district, which have the highest risk of dropout cases in Perak, were selected. A qualitative case study research design was employed. This entailed examining the subjective experiences of students at a particular school who were at risk of leaving school. Documents from the Perak State Education Department, Kinta Utara District Education Office, and all five schools were collected. In addition, fourteen semi-structured interviews were conducted with at-risk students who dropped out, five semi-structured interviews were conducted with the school counsellors, and a collage session was held with each at-risk student from the five schools to gather information on the phenomenon. The purposive sampling method was used to choose the participants, especially the at-risk students to dropped out. The obtained data were transcribed and analysed. Thematic analysis and the AI Qualitative data analysis software, ATLAS.ti, were used for coding purposes. The findings revealed three factors contributing to dropout trends among at-risk secondary school students in the Kinta Utara district: individual perspective, inner institution perspective, and outer perspective. Within these factors, several themes emerged, including student's attitude, student's perception of success, family economic status, and lack of parental support. The findings also showed that racial factors were insignificant in dropout rates among secondary school students in the Kinta Utara district. Furthermore, the study identified approaches employed by counsellors and the school to address the dropout issue. The existing approaches can be improved when necessary parties, including schools, communities, parents, NGOs, law officers, and Education Districts, work together to address the issue. The hope is that the findings obtained can serve as a parameter for the Perak State Education Department in planning strategies to address the increasing number of dropout students in the state. It may also serve as a guideline for the respective parties to understand the dropout issue from the perspective of at-risk students in managing the phenomenon of dropout among secondary school students in Malaysia.